JAMES II AND HIS ARTISTIC PATRONAGE IN SANTES CREUS: PURPOSES, SEMANTIC CONTENT AND THE INFLUENCE OF FREDERICK II. - COLL, MARTA SERRANO (Imago Temporis. Medium Aevum, 2022)
This study analyses two of the great artistic projects that James II the Just (1291-1327) promoted at the Cistercian monastery of Santes Creus (Aiguamúrcia, Tarragona, Catalonia, Spain) and which still stand to this day; namely, the dynastic pantheon and the cloister, specifically the unusual south-western pillar adjacent to the Porta Reial (Royal Entrance). The study explains the extent to which both had an aesthetic, persuasive and communicative purpose that was intended to serve the royal rhetoric and how sacredness, lineage and the role of the sovereign as executor of divine providence were key concepts for understanding the totality of these eloquent visual devices. To do this, as I will show, it is essential to examine the influences of Frederick II of Sicily, in particular the legal code known as the Liber Augustalis.